1956
DOI: 10.1139/b56-058
|View full text |Cite
|
Sign up to set email alerts
|

Cell Size and Survival in Conifer Cambium

Abstract: TJse pseudotr,~tlsverse divisions o f fusiforin ii1itiaIs Fly which the caanbi~~ni of coizifers is accornrmodnted t o iilcrcasing girth te:id to occrlr a t reIntivr.ly high rates of freslur.nc.y. The o\-erprociuctiora of izew iuitiiils is accoir~panied bt exterlsive ccll lo-s. The co~~tinta;ltioii c>r retluction o f fusiforrn i~iiti~ils after origin 111 anticli11,ll divisio~l is evitltl~ltlp related t o CPII length ;iiltl eutent of r,lv coilt,icts. The I'lrgcst fusiforln irliti,rls gciacrnlly s~rrvive and rcpe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

1961
1961
2009
2009

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 2 publications
1
17
0
Order By: Relevance
“…Scale bar in A is 500 µm and also for B and E, F; scale bar in C is 100 µm and also for D and G; and scale bar in H is 25 µm, also for I famous length-on-age curve (Sanio curve) was then established, which indicated that tracheids generally increase in length from the central wood outwards, until a certain size is reached, after which they remain constant in the later stages of secondary growth. Later, the Sanio curve was also confirmed in many other terrestrial species (e.g., Bailey 1920Bailey , 1923Bisset et al 1951;Spurr and Hyvarinen 1954;Bannan and Bayly 1956;Dinwoodie 1961;Carlquist 1975Carlquist , 1988Baas 1976;Gartner 1995) and widely accepted as a common size variation Results are means ± SD. Different letters within the same character indicate significant difference at 5% level (Fisher's test) pattern for tracheary elements in gymnosperms and typical woody dicotyledons with nonstoried wood, although some investigations on succulent plants and dicotyledon rosette shrubs showed deviations from the classic Sanio curve (Carlquist 1962(Carlquist , 1975(Carlquist , 1988Mabberley 1974).…”
Section: Discussionmentioning
confidence: 67%
“…Scale bar in A is 500 µm and also for B and E, F; scale bar in C is 100 µm and also for D and G; and scale bar in H is 25 µm, also for I famous length-on-age curve (Sanio curve) was then established, which indicated that tracheids generally increase in length from the central wood outwards, until a certain size is reached, after which they remain constant in the later stages of secondary growth. Later, the Sanio curve was also confirmed in many other terrestrial species (e.g., Bailey 1920Bailey , 1923Bisset et al 1951;Spurr and Hyvarinen 1954;Bannan and Bayly 1956;Dinwoodie 1961;Carlquist 1975Carlquist , 1988Baas 1976;Gartner 1995) and widely accepted as a common size variation Results are means ± SD. Different letters within the same character indicate significant difference at 5% level (Fisher's test) pattern for tracheary elements in gymnosperms and typical woody dicotyledons with nonstoried wood, although some investigations on succulent plants and dicotyledon rosette shrubs showed deviations from the classic Sanio curve (Carlquist 1962(Carlquist , 1975(Carlquist , 1988Mabberley 1974).…”
Section: Discussionmentioning
confidence: 67%
“…On the other hand, the symplastic growth causes uniform elongation of neighboring cells so that the adjacent walls neither alter their mutual position nor new contacts between cells are formed. As per current concept, the cambial surface thus produced is normally in excess and, therefore some of the initial cells are made to be lost (Bannan and Bayley 1956;Hejnowicz 1961Hejnowicz , 1968Hejnowicz and Brański 1966).…”
Section: Introductionmentioning
confidence: 99%
“…An obstacle to these processes such as in a harsh environment like water deficit results in the reduced length of vessel elements and fibers due to retarded intrusive growth. Although low frequencies of pseudotransverse division in the cambium tend to increase cell length as reported by Bannan and Bailey (1956) in conifer cambium and Philipson et al (1971), the resultant increase of cell length in dwarf trees is not as great as might be expected since the loss of initials is reduced. Therefore, this small loss of initials would not allow the space for elongation of the surviving daughter initials.…”
Section: Discussionmentioning
confidence: 57%